2014
DOI: 10.2298/vsp1405467r
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of substance use among adolescents and its correlation with social and demographic factors

Abstract: Stable family, lower amount of pocket money weekly and good school performance are protective factors in prevention of substances use among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
2
8
1
2
Order By: Relevance
“…Our finding of male predominance among drug users is concordant with previous studies that showed males had a higher prevalence of substance use than females [ [ 35 , 38 , 39 ]]. Abbadi et al investigated tobacco usage among adolescents of grades 9th to 12th in Jordan and found that approximately one-third of students were cigarette and/or waterpipe smokers, and males had higher rates of nicotine dependence than females [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of male predominance among drug users is concordant with previous studies that showed males had a higher prevalence of substance use than females [ [ 35 , 38 , 39 ]]. Abbadi et al investigated tobacco usage among adolescents of grades 9th to 12th in Jordan and found that approximately one-third of students were cigarette and/or waterpipe smokers, and males had higher rates of nicotine dependence than females [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, the authors found that School truancy, loneliness, sleeping problems, sadness, and poverty were associated with substance use [ 34 ]. Rakić et al investigated the prevalence of illicit drug use among 594 adolescents in Novi Sad, Serbia, and reported 10.67% (13.65% males and 8.30% females) [ 35 ]. On the other hand, higher prevalence rates of substance use were reported among students in other developing countries, such as Ethiopia (47.9%) and Sudan (31%) [ [ 36 , 37 ]].…”
Section: Discussionmentioning
confidence: 99%
“…Among the sociodemographic factors that influence alcohol intake, the negative effects on young adolescents are more serious than those on older adolescents [ 22 ]. Gender is related to the alcohol consumption of adolescents, among whom males drink more alcohol than females [ 23 , 24 , 25 ]. Compared with girls, boys are more expected to have the characteristics associated with excessive drinking, such as aggression [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms used to obtain a random sample of households and respondents represent a combination of two Brought to you by | MIT Libraries Authenticated Download Date | 5/10/18 2:07 PM cause of the frequency and extent of its use and its impact on the health of adolescents (7). Studies of alcohol consumption among European adolescents (ESPAD) indicate that the use of alcohol among young people in almost all European countries is on the rise (8), despite the fact that much research shows that high school students are well informed about the health risks arising from the consumption of alcohol (9).…”
Section: Data Source and Type Of Studymentioning
confidence: 99%